The role of fluorescent carbon dots in crops: Mechanism and applications. Issue 2 (24th May 2022) - Guo, Baoyan; Liu, Guo; Wei, Haopeng; Qiu, Jiemin; Zhuang, Jianle; Zhang, Xuejie; Zheng, Mingtao; Li, Wei; Zhang, Haoran; Hu, Chaofan; Lei, Bingfu; Liu, Yingliang
Abstract: Fluorescent carbon dots (CDs) have been widely studied in biosensing, imaging, information encryption, and optoelectronic devices due to excellent optical properties, such as photostability, tunable luminescence range, and resistance to photobleaching. In recent years, CDs have been explored for use in agriculture. Based on their light harvest and light conversion capacity, as well as their characteristics of easy synthesis and low toxicity, CDs show great potential in improving crop photosynthesis. In addition, CDs can also be used for smart and anticounterfeiting packing, food safety detection, and preservation of crops after harvest. In this study, the application of CDs with excellent optical properties in crops has been summarized, including preharvest processes (photosynthesis and plant imaging), and postharvest processes (crop preservation and food safety). Then the toxicity of CDs to crops is introduced. Finally, the present challenges and future prospects are discussed. Abstract : Fluorescent carbon dots (CDs) have excellent optical properties, so they have been widely studied and applied in crops to improve photosynthesis and thus increase crop yield. This study summarizes the mechanism and application of fluorescent CDs in crops including pre‐ and postharvest, and also discusses the toxicity of CDs. The conclusion of this paper will provide researchers with more perspectives on the application of CDs in food production, agricultural automation, and intelligence.